Cyclic voltammetric and electrical impedance spectroscopy studies of graphene- and conductive polymer–based enzyme electrodes - Ismail, Nur Alya Batrisya; Ramli, Nurul Izzati; Abd-Wahab, Firdaus; Wan Salim, Wan Wardatul Amani (Universiti Tun Hussein Onn Malaysia, 2019)
Screen-printed carbon electrodes (SPCEs), modified with graphene oxide and poly(3,4-ethylenedioxythiophene):polystyrenesulfonic acid (GO-PEDOT:PSS/SPCEs), and SPCEs modified with partially reduced GO and PEDOT:PSS (prGO-PEDOT:PSS/SPCEs) were studied for electrochemical transduction. Randles-Sevcik analysis showed that the prGO-PEDOT:PSS/SPCE has a higher effective surface area of 219.3 μm2 in comparison to the unreduced GO-PEDOT:PSS/SPCE (87.0 μm2) and the bare SPCE (71.7 μm2). Using electrical impedance spectroscopy (EIS), we determined that the prGO-PEDOT:PSS/SPCE has a lower charge-transfer resistance (Rct) of 163.82 Ω in comparison to the GO-PEDOT:PSS/SPCE (427.87 Ω) and the bare SPCE (13.31 kΩ). Glucose oxidase (GOx) was immobilized on all electrode types, including GO/SPCE as additional control and tested with low (0.2 mM), intermediate (0.6 mM), and high (1 mM) glucose concentrations. GOx/GO/SPCEs showed the largest change in anodic peak current (Ipa), 8.5, 7.5 and 4.9 μA for low, intermediate, and high glucose concentrations, respectively. Interestingly, GOx/prGO-PEDOT:PSS/SPCEs have no change in both anodic and cathodic peak current, although they exhibit better redox capability, while GOx/SPCEs have very low Ipa. The results show that the high effective surface area and low charge-transfer resistance (Rct) of prGO-PEDOT:PSS/SPCEs do not necessarily result in a sensitive glucose sensor in cases where immobilization of enzymes on the material can affect electron transfer.